Construction of hybrid multi-shell hollow structured CeO2–MnOx materials for selective catalytic reduction of NO with NH3. Issue 10 (18th January 2017) - Ma, Kaili; Zou, Weixin; Zhang, Lei; Li, Lulu; Yu, Shuohan; Tang, Changjin; Gao, Fei; Dong, Lin
Abstract : Multi-shell CeO2 –MnO x hollow spheres with superior catalytic performance were prepared via modification of the calcination rate. Abstract : Hollow structured CeO2 –MnO x hybrid materials with up to three shells were prepared successfully by using carbon spheres as the hard template. It was found that the shells could be well controlled by simply adjusting the calcination rate. Elemental mapping results showed Mn and Ce species exhibited a homogeneous spatial distribution and the existence of Mn could improve the diffusion of CeO2 into the carbon spheres during the construction of the multi-shell structure, suggesting the intensive cooperative interaction between Mn and Ce. When triple-shell CeO2 –MnO x hollow spheres were used as a catalyst for selective catalytic reduction of NO with NH3, superior low-temperature catalytic performance was exhibited, compared with traditional CeO2 –MnO x nanoparticles, single-shell and double-shell hollow spheres. Combined with XRD, H2 -TPR and XPS characterization, it was indicated that the synergistic effects and surface active species enhanced by the special multi-shell CeO2 –MnO x hollow structures could account for the excellent performances. The results of the present study shed light on the creation of complex and hybrid hollow structured materials for superior performance in catalysis fields, like NO reduction for environmental protection.